2008
DOI: 10.1177/1078155208094453
|View full text |Cite
|
Sign up to set email alerts
|

The impact of computerized prescribing on error rate in a department of Oncology/Hematology

Abstract: The impact of computerized prescribing on adverse drug events requires further evaluation. Prescriber training may be important in further reducing errors. The implementation of all the existing functions of the electronic system should lead to further reduction in errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…In total, seven unique quantitative and two unique qualitative papers met the eligibility criteria for the systematic review ( Figure 1). The research designs described in the quantitative studies included 2-arm trials [17][18][19][20] and pre-post study designs [21][22][23] . The subsection that follows describes the outcomes of the review as they relate to the original research questions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, seven unique quantitative and two unique qualitative papers met the eligibility criteria for the systematic review ( Figure 1). The research designs described in the quantitative studies included 2-arm trials [17][18][19][20] and pre-post study designs [21][22][23] . The subsection that follows describes the outcomes of the review as they relate to the original research questions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In a much larger study, Small et al 18 also compared manual and computerized complex chemotherapy prescriptions. The error rate was 20.4% in manual orders; in computerized orders, it was 11.8%.…”
Section: The Impact Of St Cpoe On Medication Errorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The review that is investigating the effect of CPOE on medication errors showed that it decreased chemotherapy related medication errors in % studies . When manual and computerized chemotherapy prescriptions compared; the error rate was found 20.4% in manual orders and 11.8% in computerized orders and the relative risk (RR) was decreased by 42% (Small et al, 2008).…”
Section: 1699 Medication Errors In Chemotherapy Preparation and Admimentioning
confidence: 99%